1999
DOI: 10.1016/s0896-6273(00)80688-1
|View full text |Cite
|
Sign up to set email alerts
|

Viral Gene Delivery Selectively Restores Feeding and Prevents Lethality of Dopamine-Deficient Mice

Abstract: Dopamine-deficient mice (DA-/- ), lacking tyrosine hydroxylase (TH) in dopaminergic neurons, become hypoactive and aphagic and die by 4 weeks of age. They are rescued by daily treatment with L-3,4-dihydroxyphenylalanine (L-DOPA); each dose restores dopamine (DA) and feeding for less than 24 hr. Recombinant adeno-associated viruses expressing human TH or GTP cyclohydrolase 1 (GTPCH1) were injected into the striatum of DA-/- mice. Bilateral coinjection of both viruses restored feeding behavior for several months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 49 publications
(7 reference statements)
8
69
0
Order By: Relevance
“…To restore dopamine synthesis in the nigrostriatal pathway using a gene transfer approach, expression of three genes would need to be achieved. The genes for TH, for TH co-factor tetrahydrobiopterin (GTP-cyclohydroxylase-1), and for AADC would all have to be successfully expressed to synthesize dopamine in situ (14,19,28,35). In addition to the problems associated with delivering three genes at appropriate levels, the regulation of dopamine levels would be difficult to control using this approach.…”
Section: Discussionmentioning
confidence: 99%
“…To restore dopamine synthesis in the nigrostriatal pathway using a gene transfer approach, expression of three genes would need to be achieved. The genes for TH, for TH co-factor tetrahydrobiopterin (GTP-cyclohydroxylase-1), and for AADC would all have to be successfully expressed to synthesize dopamine in situ (14,19,28,35). In addition to the problems associated with delivering three genes at appropriate levels, the regulation of dopamine levels would be difficult to control using this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, co-expression of a reporter gene with a therapeutic gene is frequently desired to select genetically modified cells ex vivo or identify transduced cells in vivo. Previously, different genes have been delivered either by separate viral vectors 14,45 or bicistronic vectors incorporating the IRES. [24][25][26] While the first approach is laborious and time-consuming, the second strategy can be limited by the reduced expression of the gene inserted downstream of the IRES.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Numerous studies have demonstrated the ability of these vectors to mediate efficient and long-lasting gene expression in different tissues of immunocompetent animals. [6][7][8][9][10][11][12][13][14] Recently, progress has been made in identifying positions within the AAV capsid proteins that tolerate small insertions of targeting ligands without significantly affecting resultant viral titers. [15][16][17] Moreover, rAAV genomes can be packaged into capsids derived from other AAV serotypes, rendering them more efficient in infecting certain cell types.…”
Section: Introductionmentioning
confidence: 99%
“…These DA-deficient mice cannot make DA, and are born normal but fail to thrive, have decreased food intake, gradually become hypoactive and hypophagic, and die at 3 weeks of age [301]. However, intervention and treatment of the mice with L-DOPA to restore striatal DA levels to 10% of the levels in normal mice is sufficient to elicit normal feeding behavior and animal survival [302]. Moreover, restoration of tyrosine hydroxylase gene expression using gene therapy was able rescue the deficient feeding behavior in these DA-deficient mice [303].…”
Section: Reviewmentioning
confidence: 99%